Gambaran Kualitas Hidup Pasien Dengan Penyakit Ginjal Kronik Yang Menjalani Hemodialisis Di RSAU dr. Esnawan Antariksa - Elsabet Yuni Asih; Yenny; Yohanes Gamayana Trimawang Aji (LPPM ITEKES Mahardika, 2022)
Background: Chronic kidney disease is a serious global health problem, increasing from year to year and causing an increase in morbidity and mortality. Globally, the prevalence of chronic kidney disease in 2017 increased by 21.3% and the mortality rate increased by 41.5% from 1990 to 2017 (Cockwell & Fisher, 2020). Due to kidney failure to remove metabolic waste products, it is necessary to do kidney replacement therapy, one of which is hemodialysis. Hemodialysis measures can affect the quality of life of patients from the domain of physical, psychological, social and environmental health. Objective: To describe the quality of life of patients with chronic kidney disease undergoing hemodialysis. Methods: This study used a descriptive design with quantitative methods. The population in this study amounted to 147 people. Determination of the sample using the Convenience Sampling technique as many as 60 people. Collecting data using a quality of life scale from the World Health Organization Quality Of Life (WHOQOL-BREF) which contains 24 question items covering the domains of physical, psychological, social and environmental relationships and 2 general question items regarding quality of life. The analysis used is univariate test. Results: This study showed moderate quality of life in the physical health domain (58.3%), psychological domain (86.7%), social relations domain (80.6%) and environmental domain (70%). Conclusion: The description of the quality of life of the respondents in this study shows a moderate category for all health domains